1997
DOI: 10.1002/(sici)1096-911x(199703)28:3<216::aid-mpo13>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Malignant peripheral nerve sheath tumor arising in a “de novo” ganglioneuroma: A case report and review of the literature

Abstract: A case of a “de novo” ganglioneuroma showing a large area of malignant peripheral nerve sheath tumor (MPNST) is described. The tumor arose in an 11.5‐year‐old girl with neither stigmata nor family history of von Recklinghausen's neurofibromatosis. In addition, the patient had no previous history of a neuroblastoma or radiation therapy. This report provides new evidence that, although rare, the spontaneous development of an MPNST in a benign ganglioneuroma can occur. Immunohistochemical and electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Malignant transformation into MPNST has been reported. 90,91 Schwannoma, a peripheral nerve sheath tumor consisting of well-differentiated Schwann cells, is usually encapsulated, and its cut surfaces have a pink, white, or yellow appearance. 66 Retroperitoneal tumors are large and may have areas of cystic degeneration Fig 9. -Axial contrast-enhanced computed tomography demonstrates a heterogeneous nonadipocytic, largely necrotic upper retroperitoneal mass along the aorta (stent graft in place) and pulmonary metastases.…”
Section: Neurogenic Tumorsmentioning
confidence: 69%
“…Malignant transformation into MPNST has been reported. 90,91 Schwannoma, a peripheral nerve sheath tumor consisting of well-differentiated Schwann cells, is usually encapsulated, and its cut surfaces have a pink, white, or yellow appearance. 66 Retroperitoneal tumors are large and may have areas of cystic degeneration Fig 9. -Axial contrast-enhanced computed tomography demonstrates a heterogeneous nonadipocytic, largely necrotic upper retroperitoneal mass along the aorta (stent graft in place) and pulmonary metastases.…”
Section: Neurogenic Tumorsmentioning
confidence: 69%
“…Surgical excision is usually sufficient treatment, but metastasis has been reported in ganglioneuromas, representing maturation of neuroblastoma [13]. Rarely, ganglioneuroma may reveal malignant transformation, most commonly malignant peripheral nerve sheath tumor, considering de novo ganglioneuroma or that derived from maturation in a neuroblastoma [14,15]. Thus, regular follow-up is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…19 Ganglioneuroma is a welldifferentiated tumor, most commonly seen in children older than 10 years. 20 Interestingly, Moschovi et al 21 and Kulkarni et al 22 described the malignant transformation of dormant ganglioneuroma, and Drago et al 23 reported the spontaneous development of a malignant peripheral nerve-sheath tumor in benign ganglioneuroma. Thus, careful monitoring may be necessary after the resection of benign retroperitoneal tumors.…”
Section: Discussionmentioning
confidence: 99%